2017
DOI: 10.1590/1519-6984.05116
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forages: morphoanatomy of plants grown in areas with the death of pasture syndrome

Abstract: Roots and leaves of Panicum maximum Tanzânia, Mombaça and Massai; Urochloa brizantha Piatã, Marandu and Xaraés; Urochloa humidicola Llanero; Urochloa ruziziensis Ruzizienses; Urochloa hybrida Mulato II and Cynodon nlemfuensis Estrela-roxa were analyzed, seeking to identify characters for better adaptation to the environment that may interfere with digestibility of tissue from the point of view of the rumen in cattle. Were planted ten cultivars in a completely randomized blocks with three repetitions. Was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The vascular bundles present collateral disposition surrounded by sclerenchymatous tissue and xylem differentiated into protoxylem and metaxylem. According to Ribeiro Júnior et al (2017), a more extensive arrangement of the protoxylem may associate with the anatomy of the vascular cylinder, as the bundles of the metaxylem and phloem are smaller and do not occupy so much space.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular bundles present collateral disposition surrounded by sclerenchymatous tissue and xylem differentiated into protoxylem and metaxylem. According to Ribeiro Júnior et al (2017), a more extensive arrangement of the protoxylem may associate with the anatomy of the vascular cylinder, as the bundles of the metaxylem and phloem are smaller and do not occupy so much space.…”
Section: Discussionmentioning
confidence: 99%
“…Pastures in the Northern region of Brazil, mainly formed by Marandu grass, have been and are being degraded due to excess water in the soil (Andrade & Valentim, 2007). In M. maximus, cultivars BRS Tamani and BRS Quênia, recently released hybrids (Embrapa Gado de Corte, 2015; Jank et al, 2017), are susceptible to excess water in the soil, however, cultivars such as Mombaça, BRS Zuri and Massai (Schiavo, Laura, & Jank, 2009;Mass Junior, Domiciano, Ribeiro, & Pedreira, 2016;Ribeiro-Júnior et al, 2017) have been indicated to increase pasture persistence in poorly drained sites. Pasture death has also been observed after recurrent years of water deficit, mainly in transition areas with the Caatinga Biome, and M. maximus cultivars such as Massai and others (Veras et al, 2020) have been used as alternatives.…”
Section: Introductionmentioning
confidence: 99%